Dampak Letak Buah Pada Pohon dan Perlakuan Benih Terhadap Perkecambahan Benih Kakao (Theobroma cacao L.) - Fauzi, Ahmad; Faisal, Faisal; Rafli, Muhammad (Faculty of Agriculture, Universitas Malikussaleh, 2017)
This study aims to determine the effect of the location of fruit on trees and treatment on seeds to germination cocoa. This study was conducted in Tumpok Teungoh Village, Banda Sakti Sub-district, Lhokseumawe City, August to September 2016. This study used Completely Randomized Design with 3 replications. Two factors studied were (a) the location of the fruit on the tree where L1 = The location of the fruit on the stem and L2 = The location of the fruit on the branch. (b) treatment factor in seeds where P1 = Without pulp clearance, P2 = Pulp cleansing. The parameters observed were potential growth, germination, vigor index, growth rate and synchronization of cocoa seed growth. The result of variance analysis showed that the fruit difference treatment did not affect the observation of maximum growth potential and cocoa seed germination, but it influenced the observation of vigor index, growth rate and synchronization of cocoa seed growth. Treatment of pulp cleansing did not affect the observation of growth potential, germination, growth rate and synchronization of seed growth, but pulp cleansing treatment had an effect on observation of vigor index of cocoa seed. There was no interaction between fruit difference treatment and treatment of cocoa bean pulp cleansing of all observed parameters